The association between subjective anti-doping knowledge and objective knowledge among Japanese university athletes: a cross-sectional study - Murofushi, Yuka; Kamihigashi, Etsuko; Kawata, Yujiro; Yamaguchi, Shinji; Nakamura, Miyuki; Fukamachi, Hanako; Aono, Hiroshi; Takazawa, Yuji; Naito, Hisashi (Frontiers in Sports and Active Living, 2023)
This study aimed to assess the association between subjective anti-doping knowledge (subjective ADK) and objective anti-doping knowledge (objective ADK) among Japanese university athletes, framed within the context of the Theory of Planned Behavior. Eligible participants were 486 university athletes (320 men [65.8%], 166 women; mean age of 18.9 ± 1.0 years). The participants categorized themselves in terms of quality of their anti-doping knowledge. This assessment resulted in an independent variable coded as “1: Substantial lack of adequate knowledge,” “2: Some lack of adequate knowledge,” “3: Fair amount of knowledge” or “4: Good amount of knowledge.” Objective ADK was assessed using the ALPHA test, a set of questions derived from the Athlete Learning Program about Health and Anti-doping (ALPHA) – a former World Anti-Doping Agency e-learning program. The test comprises12 questions (four choices each; passing index: ≧10 points or 80% correct answer rate). ANCOVA was conducted using subjective ADK as an independent variable, and ALPHA scores as dependent variable, adjusting for confounding factors (anti-doping experience). The ALPHA corrected answer rate across subjective ADK levels for the group were 73.10% for “1: Substantial lack of adequate knowledge,” 71.97% for “2: Some lack of adequate knowledge,” 75.18% for “3: Fair amount of knowledge” and 72.86% for “4: Good amount of knowledge.” Comparison between different levels of subjective ADK revealed no significant differences in ALPHA score considering main effects, or any of their interactions. The present results revealed that Japanese university athletes’ subjective ADK did not match their objective ADK. In the context of the Theory of Planned Behavior, there may be limitations in the perceived behavioral control in anti-doping knowledge. Even if athletes view doping as a wrongful act and have formed attitudes and subjective norms to comply with the rules, the results suggest that errors may occur in the composition of behavioral intentions due to a lack of knowledge. This could lead to the possibility of facing the risk of unintentional anti-doping rule violations. It highlights the need for targeted educational interventions to align athletes’ subjective ADK with their objective ADK.